2014
DOI: 10.1371/journal.pone.0107987
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of NBS-Encoding Genes in Malus x domestica and Expansion of NBS Genes Family in Rosaceae

Abstract: Nucleotide binding site leucine-rich repeats (NBS-LRR) disease resistance proteins play an important role in plant defense against pathogen attack. A number of recent studies have been carried out to identify and characterize NBS-LRR gene families in many important plant species. In this study, we identified NBS-LRR gene family comprising of 1015 NBS-LRRs using highly stringent computational methods. These NBS-LRRs were characterized on the basis of conserved protein motifs, gene duplication events, chromosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 58 publications
1
56
1
Order By: Relevance
“…Most studies identified variable numbers of NBS-LRR genes ranging from 50 in papaya (Porter et al, 2009) to 1,015 in apple (Arya et al, 2014). The NBS-LRR genes are unevenly distributed in plant genomes and are often found in clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies identified variable numbers of NBS-LRR genes ranging from 50 in papaya (Porter et al, 2009) to 1,015 in apple (Arya et al, 2014). The NBS-LRR genes are unevenly distributed in plant genomes and are often found in clusters.…”
Section: Introductionmentioning
confidence: 99%
“…This ATP-bound form of RPS5 engages in downstream signaling molecules that activate the defense response (Ade et al, 2007;Qi et al, 2012). More than 50 NBS-LRR R-genes, including the almost 40 CC-NBS-LRR, conferred resistance against several pathogens in plants such as Arabidopsis, tomato, potato, barley, rice, maize, apple, grape, lettuce, pepper, sunflower, melon, and soybean (Kortekamp et al, 2008;Joshi and Nayak, 2011;Kar et al, 2013;Arya et al, 2014).…”
Section: Expression Analysis Of Vfrps5-like Genesmentioning
confidence: 99%
“…Tritici, the pathogen of powdery mildew disease. Arya et al (2014) reported that expression of 18 out of 26 Malus × domestica NBS genes (MdNBS gene) was induced, while expression of other MdNBS genes was not observed under attacks of several pathogens and insects. Kortekamp et al (2008) also reported that the CC-NBS-LRR family gene, VRP1, was induced during pathogen attack in the resistant grapevine cultivar 'Gloire de Montpellier' .…”
Section: Expression Analysis Of Vfrps5-like Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…PR proteins include enzymes and antimicrobial peptides that play important roles in plant disease resistance, but they act at the later stages of plant defense responses. In effector-triggered immunity (ETI), plants deploy disease resistance proteins (R proteins) to interact with pathogenproduced effector proteins in a gene-for-gene manner at the early stage to mount a rapid and robust defense response (Martin et al, 2003;Jones and Dangl, 2006;Cui et al, 2015).The largest group of R genes encode intracellular nucleotide binding domain and leucine-rich repeat (NLR) receptors and these NLRs are highly amplified in plants (McHale et al, 2006;Arya et al, 2014;Zhong et al, 2015), but it is not known whether any of these R genes is regulated by sugars.…”
Section: Introductionmentioning
confidence: 99%